MAKNA PERJUANGAN DALAM NOVEL INDONESIA BERLATAR PERANG KEMERDEKAAN (TINJAUAN NEW HISTORICISM GREENBLATT) - Wicaksono, Andri (Universitas Pendidikan Indonesia, 2018)
Through this new approach of historicism, this study aims to reveal the construction of the meaning of